2023
DOI: 10.21203/rs.3.rs-2456088/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Childhood trauma and depressive level among non-clinical Chinese college students: the roles of rumination and perceived stress

Abstract: Background: Childhood trauma is one of major risk factors to depression, and the incidence of depression among college students has been increasing. Previous studies have validated the effect of childhood trauma on depressive level. But few studies based on the Diathesis-stress theory to investigate the role of perceived stress in the pathway between childhood trauma and depressive level, as well as considering the role of rumination. Methods: We recruited 995 non-clinical Chinese college students and ask them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…These studies have shown greater childhood trauma leads to higher levels of depression by increasing rumination. Wang et al ( 2023 ) showed that rumination moderated the relationship between childhood trauma and depression. Mao et al ( 2023 ) demonstrated that rumination partially mediated the effect between childhood trauma and trait depression, suggesting the negative influence of childhood trauma on depression was influenced by ruminative levels.…”
mentioning
confidence: 99%
“…These studies have shown greater childhood trauma leads to higher levels of depression by increasing rumination. Wang et al ( 2023 ) showed that rumination moderated the relationship between childhood trauma and depression. Mao et al ( 2023 ) demonstrated that rumination partially mediated the effect between childhood trauma and trait depression, suggesting the negative influence of childhood trauma on depression was influenced by ruminative levels.…”
mentioning
confidence: 99%